PENURUNAN KADAR Pb DALAM KERANG HIJAU (Mytilus virids) DENGAN FILTRAT TOMAT (Solanum lycopersicum) Tahun 2016 - Adistya Galih P; Narwati .; Bambang Sunarko (Poltekkes Kemenkes Surabaya, 2016)
Green mussels on the Kenjeran beach contains 1.833 mg / kg heavy metals Pb. Excessively accumulated heavy metals in the body can lead to death or illness in a short time. This study aims atdetermining the difference levels of Pb decreased in green mussel (Mytilusvirids) with a different concentration of the filtrate tomatoes.This study is an experimental research using one group pretest posttest design.The dependent variable in this study is the heavy metals Pb concentration in green mussel. The independent variable is the filtrate tomatoes concentration (25%, 50%, 75%, 100%) with 60 minutes soaking time. To determine the decrease levels effect of heavy metals Pb concentration, researcheruses One Way Anova test becausethe data has normal distribution.The results shows that the average content of Pbbefore treatment (control) is 0.20 mg / Kg. Afterthe treatment, the highest decrease of Pb is at 75% concentration that is 0.12 mg / kg with a percentage decrease of 60%.It can be concluded that there is an influence of filtrate tomatoes concentration to decreased levels of heavy metals Pb in green mussel. It is suggested to people to soak the mussels before consumption by using tomatoes filtrate because it can reduce the level of heavy metals Pb contained in crestacea, especially green mussel. Keywords : green mussels, heavy metals Pb, tomato filtrate